Efficacy of prebiotics, probiotics, and synbiotics on laying hens and broilers challenged with salmonella enteritidis - Murate, Leticia S.; Paiao, Fernanda G.; Almeida, Adriana M. de [UNESP]; Berchieri, Angelo [UNESP]; Shimokomaki, Massami (Japan Poultry Science Assoc, 2015)
This study aimed to evaluate the efficacy of dietary prebiotic, probiotic, and symbiotic products for controlling infection in laying hens and broiler chickens challenged with Salmonella enterica serovar Enteritidis (SE). These products could replace the use of antibiotics, which would avoid the problem of hastening antimicrobial resistance for both types of birds. Salmonella-free 1-day-old (1-d-old) layers chicks and broilers chicks were inoculated with SE resistant to nalidixic acid and spectinomycin (SE Nai(r) Spec(r)) and divided into four groups: 1) control (without feed additives); 2) probiotic (Bacillus subtilis, Lactobacillus acidophilus, L. casei, Enterococcus faecium, Bifidobacterium longum); 3) prebiotic (inulin, fructooligosaccharide, mannanoligosaccharide, and oligosaccharide); and 4) synbiotic (85% of the probiotic + 15% of the prebiotic additives). The presence of SE Nal(r) Spec(r) in cloacal swabs was analyzed at 7, 14, and 21 days post-infection (dpi) in laying hens and broilers. The number of SE Nai(r) Spec(r). per gram of cecal contents was determined at 7, 14, and 21 dpi in laying hens and at 2, 5, 7, 14, and 21 dpi in broilers. The results showed that the prebiotic additive reduced the occurrence of SE in cloacal swabs from laying hens but not from broilers. In the groups of laying hens and broilers that received prebiotics, the isolation and counts of SE Nair Specr were lower during the first week post-infection but not throughout the experiment. The probiotic and synbiotic additives did not influence the SE infection in laying hens and broilers; in contrast prebiotics had a protective effect during the first week post-infection.
Keywords: Additives; Chicken; Pathogenic bacteria; Salmonella-free